STREET BEGGING IN THE TAMALE METROPOLIS: EVOLUTION, DIMENSIONS AND EFFECTS - Longi, F. Y. T.; Abdulai, A.; Rashid, Z. A. (UDS International Journal of Development, 2022)
Begging on the streets in the Tamale metropolis has metamorphosed over the years with most beggars employing various strategies including using children as aides/guides while others disguise and exaggerate their physical conditions to use as baits to attract sympathy and alms. The objective of this paper is to explore the evolution, the dynamics, dimension and effects of street begging on pedestrians/society, the beggars and the children they use as aids. The participants were beggars especially those who use children to beg. Others were key informants from Tamale Metropolitan Assembly and Department of Children and members of the public (almsgivers and non-givers) and diviners who prescribe the sort of alms people should give. The study used the mixed methods though largely qualitative in nature and data was analysed both manually (content analysis) and with the help of computer software (SPSS version 20). Purposive, convenience/accidental sample techniques were used to select the respondents. The study revealed that disability, poverty and cultural beliefs were the main underlying factors which compelled individuals to resort to begging. Beggars saw themselves as incapable and therefore deserved public sympathy. Hired children accepted begging since they earned a living from it through the motivations and â€œpaymentsâ€. Children of relatives under the care of adult beggars enjoy fewer benefits as compared to biological children. From this study, not all almsgivers gave to improve a beggarâ€™s life but to solve their own problems. The beggars in this study were not aware that begging was illegal in Ghana, punishable by law Keywords: Street begging, alms giving, child beggars, evolution, effects